Prognostic Significance of Triglyceride-Glucose Index for Adverse Cardiovascular Events in Patients With Coronary Artery Disease: A Systematic Review and Meta-Analysis - Luo, Jin-Wen; Duan, Wen-Hui; Yu, Yan-Qiao; Song, Lei; Shi, Da-Zhuo (Frontiers in Cardiovascular Medicine, 2021)
Background: Insulin resistance (IR) represents a critical regulator in the development and progress of coronary artery disease (CAD). Triglyceride-glucose (TyG) index, a novel surrogate biomarker of IR, has been implicated in several cardiovascular disease. Accordingly, we conduct a meta-analysis to elucidate the relationship between TyG index and adverse cardiovascular events in patients with CAD. Methods: To identify the studies examining the predictive capacity of TyG index for adverse cardiovascular events in the setting of CAD, we performed a comprehensive literature retrieval of Scopus, PubMed, EMBASE, as well as Web of science, from the inception of databases to October 5, 2021. We pooled the adjusted hazard ratio (HR) along with 95% confidence interval (CI) using a random-effects model. The primary outcome was a composite of major adverse cardiovascular events (MACEs), including all‑cause death, cardiovascular death (CV death), myocardial infarction (MI), stroke, hospitalization for unstable angina or heart failure, and revascularization. The secondary outcomes were all‑cause death, CV death, MI, stroke, and revascularization. Additionally, we conducted subgroup analyses stratified by the diabetes status, age, body mass index (BMI), low density lipoprotein cholesterol (LDL-C), category of TyG index, sample size, follow-up duration and study design. Results: 12 studies involving 28,795 patients with CAD were finally taken into the quantitative analysis. Our findings showed that there was a 2.14-fold higher risk of MACEs among CAD populations in the highest TyG group compared with those in the lowest TyG group (HR:2.14, 95% CI:1.69-2.71, P<0.001). A greater risk of MACEs was observed in participants with higher BMI than those with lower BMI (P=0.03 for interaction). In the analysis of secondary outcomes, we also observed a markedly increased risk of MI, stroke, and revascularization in the highest TyG group compared with the lowest TyG group. No evidence of a significant association between TyG index and CV mortality or all-cause mortality in patients with CAD was identified. Conclusions: The elevated TyG index is a promising predictive factor of adverse cardiovascular events in patients with CAD.